Method for creating functionally graded materials with spark plasma sintering and a continuous machine for future scalability - Colasuonno, Paul S., author; James, Susan, advisor; Ma, Kaka, committee member; Neilson, James, committee member (Colorado State University. Libraries, 2017)
This work develops a quantitative process to sinter functionally graded materials (FGMs) to specific porosity gradients using Spark Plasma Sintering (SPS). The powder densification in SPS is modeled using the Master Sintering Curve (MSC) calculated from shrinkage due to three different heating rates. The meaning of the apparent sintering activation energy is discussed along with the MSC's applicability to SPS. The MSC is adjusted for the additional sintering that occurs during cooling, such that porous materials can be produced by interrupting the heating schedule. The temperature in the powder is then spatially resolved by a constructed thermal-electric FEA model. Tooling is designed to apply a steady state temperature gradient (50°C/mm) on zirconia (+3% mol yttria) powder. The MSC, coupled to the thermal-electric model, is used to spatially predict densification in a temperature gradient. Resulting FGM microstructures and grain size distributions are discussed. Design problems found while attempting to scale the FGMs process to larger diameters are quantified. As an alternative to traditional SPS batch processes, a Continuous Electric Field Assisted Sintering (CEFAS) machine is developed to address these practical limitations from a new direction. The proof of concept CEFAS machine uses Joule heated rollers to continuously heat, compress, and extrude material under conditions analogous to SPS. Design considerations, lessons learned, and control variables for future iteration CEFAS machines are illustrated.
Keywords: continuous electric field assisted sintering; functionally graded materials; spark plasma sintering; electric field assisted sintering; ceramics engineering; master sintering curve